THE CONTRIBUTION OF NIGERIA TO THE ADVANCEMENT OF AFRICAN AND GLOBAL PEACE AND THE RESOLUTION OF THE LIBERIA LONG-STANDING CONFLICT - Amos Ojo Adedeji (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
Africanized solutions were born as a result of the failure of western world to sustain stability and peace in African continent. Nigeria took up the task as Africa's giant. Since the early 1990s, Nigeria has taken the helm of both international and regional peacekeeping initiatives. Nigeria makes up the fourth largest worldwide and the largest African contributor to UN peacekeeping operations. It is crucial to Nigeria's national interests to allow for sustained Nigerian participation of peacekeeping missions because Nigeria and the U.S. are a critical regional partner. This study discusses, among other things, Nigeria's contribution to the peace effort in Liberia. Based on its findings, the paper makes the case that Nigeria's participation in the Liberian peace process was primarily driven by the need to bring peace to the continent of Africa and the West Africa sub-region. This goal was attained, however, at a very high cost in terms of human and material resources. The article made the case that structural issues must be resolved in order to address the problem of conflicts in Africa.